Estimating Regulation-Induced Substitution: The Effect of the Clean Air Act on Water and Ground Pollution - Greenstone, Michael (American Economic Review, 2003)
Estimating Regulation-Induced Substitution: The Effect of the Clean Air Act on Water and Ground Pollution by Michael Greenstone. Published in volume 93, issue 2, pages 442-448 of American Economic Review, May 2003